Landing technique affects knee loading and position during athletic tasks - Cortes, N.; Morrison, S.; Van Lunen, B. L.; Onate, J. A. (Journal of Science and Medicine in Sport, 2012)
Anterior cruciate ligament (ACL) injuries have been reported to occur with the ankle in a dorsiflexed position at initial contact. Few studies have attempted to quantify the biomechanical parameters related with such landing patterns during athletic tasks.